2007
DOI: 10.1897/06-646r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Transferable properties of multi‐biological toxicity caused by cobalt exposure in Caenorhabditis elegans

Abstract: Cobalt is widespread in the environment and excess dietary Co exposure can result in toxic effects in many organisms. However, whether the multi-biological toxicities caused by Co exposure can be transferred from parents to progeny has not been clarified. In the present study, we analyzed the multiple toxicities of Co to the nematode Caenorhabditis elegans and its progeny. Endpoints of life span, body size, vulva development, brood size, generation time, body bend, head thrash, and chemotaxis plasticity were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…This early exposure to Al appears to be enough to cause phenotypic abnormalities in later life since we found no evidence for elevated whole-body Al levels in the F 1 progeny when only the P 0 was exposed to Al. Similar transferable toxicity phenotypes have been reported for worms exposed to Zn, Ni, lead (Pb) and cobalt (Co) 29-32 and it has been suggested that this phenomenon could be due to the build-up of toxic metals inside the developing egg leading to Al toxicity during embryogenesis 29,32 —a process termed ’chemical legacy’. Maternal transfer of silver (Ag), selenium (Se) and Zn to developing embryos has been reported for the cuttlefish Sepia officinalis , indicating this as a possible mechanism of action.…”
Section: Discussionsupporting
confidence: 55%
“…This early exposure to Al appears to be enough to cause phenotypic abnormalities in later life since we found no evidence for elevated whole-body Al levels in the F 1 progeny when only the P 0 was exposed to Al. Similar transferable toxicity phenotypes have been reported for worms exposed to Zn, Ni, lead (Pb) and cobalt (Co) 29-32 and it has been suggested that this phenomenon could be due to the build-up of toxic metals inside the developing egg leading to Al toxicity during embryogenesis 29,32 —a process termed ’chemical legacy’. Maternal transfer of silver (Ag), selenium (Se) and Zn to developing embryos has been reported for the cuttlefish Sepia officinalis , indicating this as a possible mechanism of action.…”
Section: Discussionsupporting
confidence: 55%
“…The toxicities of a variety of metals and metalloids have been formally assayed in C elegans and include Ag, Al, Ar, Cd, Co, Cr, Cu, Hg, Pb, Ti, Ur, and Zn (Bruinsma et al , 2008; Calafato et al , 2008; Dhawan et al , 2000; Guo et al , 2009; Jiang et al , 2009; Liao and Yu, 2005; Ma et al , 2009; Roh et al , 2009; Wang et al , 2007, 2009; Ye et al , 2008). However, studies on the toxicity of selenium have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The locomotion behavior was assessed by the endpoints of head thrash and body bend, which have been successfully explored to evaluate the neurobehavioral toxicity induced by metal exposure [17]-[18]. The heat-shock is a commonly and extensively investigated stress in nematodes [9].…”
Section: Discussionmentioning
confidence: 99%